2021
DOI: 10.3389/fgene.2021.613197
|View full text |Cite
|
Sign up to set email alerts
|

A Timely Review of Cross-Kingdom Regulation of Plant-Derived MicroRNAs

Abstract: MicroRNAs (miRNAs) belong to a class of non-coding RNAs that suppress gene expression by complementary oligonucleotide binding to the sites in target messenger RNAs. Numerous studies have demonstrated that miRNAs play crucial role in virtually all cellular processes of both plants and animals, such as cell growth, cell division, differentiation, proliferation and apoptosis. The study of rice MIR168a has demonstrated for the first time that exogenous plant MIR168a influences cholesterol transport in mice by inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 86 publications
0
33
0
Order By: Relevance
“…According to recent review report, screening of conserved plant miRNAs against the hepatitis B (HBV) and C (HCV) viruses revealed six HCV gene sequences that are likely to be targeted by miR-156, miR-157, miR-166, miR-172, and miR-390. Whilst five conserved plant miRNAs: miR-166, miR-169, miR-172, miR-390, and miR-399 that were very likely to align and interact onto the six HBV gene sequences [ 19 ]. A report from our study group also revealed a cross-species interaction of plant miRNAs belonging to the family of miR477 ubiquitously found in all three medicinal plant genomes of O. tenuiflorum , P. nigrum and Z. officinale to pinpoint a plausible role of plant derived dietary miRNAs to mediate viral mRNA silencing and provide antiviral defence against SARS-CoV-2 infection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent review report, screening of conserved plant miRNAs against the hepatitis B (HBV) and C (HCV) viruses revealed six HCV gene sequences that are likely to be targeted by miR-156, miR-157, miR-166, miR-172, and miR-390. Whilst five conserved plant miRNAs: miR-166, miR-169, miR-172, miR-390, and miR-399 that were very likely to align and interact onto the six HBV gene sequences [ 19 ]. A report from our study group also revealed a cross-species interaction of plant miRNAs belonging to the family of miR477 ubiquitously found in all three medicinal plant genomes of O. tenuiflorum , P. nigrum and Z. officinale to pinpoint a plausible role of plant derived dietary miRNAs to mediate viral mRNA silencing and provide antiviral defence against SARS-CoV-2 infection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ingested plant miRNAs remain unaffected by stomach acidification and transit through the gastrointestinal system, enter the bloodstream to reach tissues, for regulating a particular gene expression in mammals and are found to be excreted in urine [ 14 , 18 ]. The proactive influence of plant miRNA is not just reduced with being an anti-viral, but it's also proven to initiate anti-inflammatory, anti-cancer as well as immuno-regulatory affects upon regular consumption of the plant/herb decoction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhang et al defended this, saying that the results would have been based on a biased sequencing method between plants and animals (Zhang et al 2012 ; Dickinson et al 2013 ). Since then, the debate has continued based on the results by different groups of scientists who has provided evidence for or against the concept, of cross-kingdom transfer of miRNAs through various dietary sources and their regulation of mammalian genes over issues, such as methodology, contamination, and detection sensitivity (Li et al 2021 ; Chen et al 2013 ). Scientists reviewed evidences for and against the diet-derived miRNAs from plants, meat, milk, and exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…This study opened the avenue for researchers to investigate plant-derived miRNAs as potential bioactive molecules for therapeutic interventions. Food consumption is a major route for miRNA transfer from plant to animal, allowing exogenous miRNAs from the diet to influence critical cellular processes in the animal (Samad et al 2021 ; Li et al 2021 ). Emerging evidence also pointed out that such exogenous miRNAs can sustain in the human gastrointestinal tract (Mar-Aguilar et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The other obvious question concerns the potential of plant miRNAs to become new natural medicine products ( Lukasik and Zielenkiewicz, 2016 ). This subject was recently extensively reviewed e.g., ( Sanchita et al, 2018 ; Jia et al, 2021 ; Li et al, 2021 ; Samad et al, 2021 ; Winkle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%